The Influence of Work Posture and Work Duration on the Incidence of Low Back Pain Among Batik Artisans: a Cross-sectional Study: Work Posture and Work Duration - Pamungkas, Megistra; Pratama, Susilo Budi; Fatharani, Lukman Faishal (STIKes Mandala Waluya Kendari, 2024)
Background: Batik artisans, particularly those involved in the